Long-term follow-up after dilation in symptomatic esophageal intramural pseudodiverticulosis: an observational study in 22 cases - Bechtler, Matthias; Vollmer, Heiko; Vetter, Stephan; Fuchs, Erik-Sebastian; Weickert, Uwe; Jakobs, Ralf (Endoscopy, 2014)
Endoscopic bougienage seems to be the most effective therapy for dysphagia in esophageal intramural pseudodiverticulosis (EIPD), but nothing is known about the long-term success of this treatment option. This report presents long-term results for 21 of 22 patients with EIPD who were treated with bougienage. A total of 103 sessions of bougienage up to a diameter of 18 mm were performed, without major complications and with 100 % clinical success. During follow-up, symptom recurrence with further bougienage occurred in 12 /21 patients (57 %), who had variable symptom-free intervals (range 1.5 – 96 months). Symptom recurrence was associated with concomitant reflux esophagitis. Although this series demonstrates that bougienage is an effective method for relieving dysphagia in EIPD, the long-term effectiveness is limited.